Brand Relationship Quality Strategy and Brand Loyalty of Abekani's Product - Dewi Kartikaningsih (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
The rapid of fashion industry in Indonesia has created intense competition among the fashion industry players and attracted. One of the fashion is genuine leather handbag product. The manufacture of the leather bag in Indonesia is Abekani. These handmade products are in great demand because they have high quality and unique in their way of buying, namely through a closed group on Facebook. The rules made make group members loyal to Abekani products. Brand loyalty shows the existence of customer ties with certain brands marked by repeated purchases from customers. The concept of BRQ (Brand Relationship Quality) is a strategy that can be used by a brand to maintain and improve relationships with customers to remain on the brand so as to create brand loyalty. Based on the phenomenon of the unique way of buying Abekani products, makes consumers loyal to the brand and the existence of previous research on Brand Relationship Quality, with respondents being leather bag lovers in Solo with a sample of 36 with a purposive sampling .The analysis uses SPSS 24 for simple regression and the result is the Brand Relationship Quality strategy has a positive effect on Brand Loyalty Abekani Products.